Organizational and Psychosocial Working Conditions and Their Relationship With Mental Health Outcomes in Patient-Care Workers. Issue 12 (December 2019) - López Gómez, María Andrée; Sabbath, Erika; Boden, Leslie; Williams, Jessica A.R.; Hopcia, Karen; Hashimoto, Dean; Sorensen, Glorian
Abstract : Objective: The aim of this study was to investigate the relationship between both psychosocial and organizational working conditions with self-reported mental health and mental health expenditures. Methods: This study used worker survey and medical claims data from a sample of 1594 patient-care workers from the Boston Hospital Workers Health Study (BHWHS) to assess the relationship of psychosocial (job demands, decision latitude, supervisor support, coworker support) and organizational (job flexibility, people-oriented culture) working conditions with mental health outcomes using validated tools Results: People-oriented culture and coworker support were negatively correlated with psychological distress and were predictive of lower expenditures in mental health services. Job demands were positively correlated with psychological distress. Conclusions: Working conditions that promote trustful relationships and a cooperative work environment may render sustainable solutions to prevent ill mental health. Abstract : Supplemental Digital Content is available in the text